2013
DOI: 10.1002/cncr.28354
|View full text |Cite
|
Sign up to set email alerts
|

Identification of FOXM1‐induced epigenetic markers for head and neck squamous cell carcinomas

Abstract: BACKGROUND: Epigenetic reprogramming of the methylome has been implicated in all stages of cancer evolution. It is now well accepted that cancer cells exploit epigenetic reprogramming, a mechanism that regulates stem/progenitor cell renewal and differentiation, to promote cancer initiation and progression. The oncogene FOXM1 has been implicated in all major forms of human cancer. METHODS: We have recently shown that aberrant upregulation of FOXM1 orchestrated a DNA methylation signature that mimics the cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…More specifically, high expression of FoxM1 induces changes in DNA methylation and epigenetic remodeling programs to maintain stem/progenitor cell renewal and to antagonize pathways inducing differentiation [41, 42]. Modifications in the proliferative nature of stem/progenitor cells have been implicated in the initiation and recurrence of several cancers, including HNSCC and OSCC [43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, high expression of FoxM1 induces changes in DNA methylation and epigenetic remodeling programs to maintain stem/progenitor cell renewal and to antagonize pathways inducing differentiation [41, 42]. Modifications in the proliferative nature of stem/progenitor cells have been implicated in the initiation and recurrence of several cancers, including HNSCC and OSCC [43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…The large CS proteoglycan Versican is linked to poor prognosis in many different cancer types (Ricciardelli et al 2009b). Differential methylation of CHPF is induced by FOXM1 (Hwang et al 2013) Not reported (Tominaga et al 2014) and confers resistance to docetaxel in breast cancer (Honma et al 2008). Potential biomarker in colorectal cancer .…”
Section: :3mentioning
confidence: 99%
“…Consistent with this concept, using primary normal keratinocytes, Hwang et al found that overexpressing FOXM1 “brainwashed” normal cells to adopt the methylome profile of cancer cells. [95, 96] Moreover, FOXM1 is also important in stem or progenitor cell expansion, which is believed to be involved in cancer initiation. [97] Therefore, combination treatment with small molecules of JQ1 and Siomycin A[98] that target MYC and FOXM1, respectively, might serve as a promising therapeutic strategy to prevent MIC recruitment and reprogramming of surrounding bystander cells halting cancer progression and metastasis (Figure 2).…”
Section: Tumor Cell Regulation Of the Microenvironmentmentioning
confidence: 99%